Asset protection in multinational enterprises – where to now?. Issue 4 (17th November 2014) - Smith, Freya
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to shed light on the potential implications for asset protection planning in multinational enterprises (MNEs) from the Organisation for Economic Co-Operation and Development (OECD)'s work on base erosion and profit shifting (BEPS) and the global push towards increased transparency and automatic information exchange. Design/methodology/approach – An examination of the academic literature across a range of areas of the law relevant to MNEs and an analysis of the risks facing MNEs and the significance of asset protection in managing these risks. An examination of the OECD's work on BEPS and automatic information exchange and implications for asset protection strategies utilised by MNEs with a particular focus on the critical issues of disclosure, ownership and control. Findings – The full extent to which MNEs will be affected by the OECD's work on BEPS remains unknown. Early signs indicate a significant shift in the focus of tax rules away from the pricing of specific transactions between related entities to the total global value chain of an MNE opening the door for more widespread adoption of enterprise liability and for states to obtain a complete view of MNE tax and asset protection planning, potentially including previously impenetrable trusts and limited liability companies. Originality/value – This paper is one of the first to provide an analysis of the importance of asset protection to MNEs and the potential risks arising for asset protection planning in MNEs from the OECD's work on BEPS and automatic information exchange.